Mendeleyev's Dream. The Quest for the Elements - Strathern P. Paul (London, Penguin Books, 2001)
In this elegant, erudite, but entertaining book, Paul Strathern, the award-winning novelist and expositor of complex ideas, unravels the dramatic history of chemistry through the quest for the elements. Framing this history is the life story of the nineteenth-century Russian scientist Dmitri Mendeleyev, who fell asleep at his desk and awoke after conceiving the periodic table in a dream-the template upon which modern chemistry is founded and the formulation of which marked chemistry's coming of age as a science. From ancient philosophy through medieval alchemy to the splitting of the atom, this is the true story of the birth of chemistry and the role of one man's dream.